Effect of lysine levels on the performance of pigs in the early phase of growth fed with broken rice-based diets replacing corn (2015)
An experiment was conducted at the Unit for Research Support of Animal Science and Nutrition Laboratory Animal CCTA's of Universidade Estadual do Norte Fluminense, Campus dos Goytacazes, State of Rio de Janeiro, Brazil, to evaluate the effects of digestible lysine levels on growth performance in pigs in the early phase of growth fed with a diet containing broken rice in total replacement of corn. Sixty 63 days of age and 28,68±0,49kg piglets were used, distributed in a randomized complete block design with four treatments, five repetitions and three animals per replica, two males and one female. The experimental phase was 21 days. The portions were supplemented with increasing concentrations (0.00, 0.191, 0.392 and 0.573%) of synthetic lysine to compose the treatments with 0.717, 0.867, 1.017 and 1.167% of digestible lysine. The food supply was crushed and water was added at ease. Data were submitted to analysis of variance and polynomial regression. There was quadratic effect of lysine levels on daily weight gain (0.817; 0.865; 0.846 and 0.840kg), on food intake (1.540; 1.598; 1.591 and 1.553kg) and the daily energy intake (4.975; 5.161; 5.138 and 5.016kcal) and lineal effect on the dietary intake of lysine (11,04; 13,85; 16,17 and 18,24g), but there was no effect (P>0.05) of lysine levels on feed conversion (1,89; 1.86; 1,89 and 1,85). The digestible lysine requirement for higher weight gain was estimated to be 0,969% by the quadratic model for growing pigs fed with diets containing broken rice.